Biological recolonization dynamics: Kentridge's artwork disappearing along the Tiber embankments (Rome, Italy). (May 2021) - Bartoli, Flavia; Casanova Municchia, Annalaura; Leotta, Marcello; Luciano, Sebastiano; Caneva, Giulia
Abstract: In April 2016, William Kentridge realized the bio-artwork "Triumphs and Laments" along the Tiber embankments, representing a figures procession, chosen as relevant steps of Roman history. The drawing rose in negative after applying a stencil onto the homogeneous black biopatinas and removing them through a low-pressure washer. The patinas, growing on the travertine surfaces, were dominated by cyanobacteria communities, mainly composed by Chroococcus lithophilus, Myxosarcina spectabilis, Tolypothrix byssoidea, and Synechocistis pevalekii . To collect precise data on the dynamic of biological recolonization, we monitored the figure's life by 2016–2020, analyzing the progressive darkening, which gave rise to the artwork disappearance. By image analysis and color variation values (ΔE), using a detailed photographic survey (every 3–4 months) and colorimetric sampling (once in the year), we assessed the recolonization phenomena and their seasonal dynamics. A progressive relevant increase of black intensity started from the 3rd year and usually 4–5 years were sufficient for a complete recolonization. We also collected climatic data and performed elaborations on Cold and Drought Stress, which provided evident correlation among biological colonization and climatic data, with their seasonal fluctuations. When a longer duration of such bio-artwork would be required, such information will be useful in suggesting treatments. Graphical abstract: Image 1 Highlights: Long-term and in-situ monitoring of natural recolonization dynamics on travertine. Influences of temperature and rainfall in recolonization processes by cyanobacteria. Different colorimetric analyses at different scales to assess recolonization process. Ecological analysis to support preventive conservation and bio-art artworks.